2020
DOI: 10.1093/ehjci/ehaa946.0064
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and clinical outcomes after TAVI, regarding the extravalvular cardiac damage defined by echocardiography prior the procedural

Abstract: Background Recent studies have shown that the extent of extravalvular (extra-aortic valve) cardiac damage in patients with severe aortic stenosis (AS) have important prognostic implications for clinical outcomes after aortic valve replacement (AVR). Aims The aim of the present study is to evaluate the prognostic impact of a defined staging classification (“Généreux Staging Classification”) (GSC) characterizing the extent of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Finally, it should be observed that, at variance with most data in medical literature, 19,21–26 in our population, we recorded a higher rate (17.1%) of noncardiovascular than cardiovascular (10.5%) mortality. The reasons for this finding are not clear, but the inclusion of more generally compromised patients, as indicated by the high rate of ‘frail’ patients (59.6%), may at least in part explain the unusual high rate of noncardiovascular death.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Finally, it should be observed that, at variance with most data in medical literature, 19,21–26 in our population, we recorded a higher rate (17.1%) of noncardiovascular than cardiovascular (10.5%) mortality. The reasons for this finding are not clear, but the inclusion of more generally compromised patients, as indicated by the high rate of ‘frail’ patients (59.6%), may at least in part explain the unusual high rate of noncardiovascular death.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous studies have reported varying and inconsistent associations between cardiovascular events, mortality, and both clinical factors (such as age, 6 , 8 male sex, 8 , 21 presence of coronary artery disease, 22 diabetes, 23 chronic kidney disease, 8 , 20 and smoking) and echocardiographic factors (including low LVEF, 7 , 24 , 25 mean AV gradient, 7 , 26 PAPs, 7 , 9 , 23 and moderate-to-severe mitral 23 and aortic regurgitation 7 ).…”
Section: Discussionmentioning
confidence: 99%